Seismic Performance and Application of Sandwiched Buckling-Restrained Braces and Dual-Core Self-Centering Braces - Chou, Chung-Che; Chung, Ping-Ting; Chen, Ying-Chuan (Journal of Engineering and Technological Sciences, 2014)
This paper first presents cyclic test results  and  the  application  of  the proposed sandwiched buckling-restrained brace (BRB).  The proposed BRB can be easily  disassembled  in the field.  This  provides  an opportunity for inspection of  the  core  after  a  large  earthquake.  The  mechanics  and  cyclic  behavior  of  a novel  steel  dual-core  self-centering  brace  (SCB)  are  then  proposed  and introduced, followed by  the  testing of  a  dual-core SCB  in order  to evaluate  its cyclic  performance.  Both  braces  achieve  an  excellent  target  lateral  drift performance  of  up to 2.5%,  thus  satisfying  the seismic requirement by  the  AISC Seismic Provisions 2010.